2021
DOI: 10.1002/solr.202000771
|View full text |Cite
|
Sign up to set email alerts
|

Dopant‐Free Bifacial Silicon Solar Cells

Abstract: Herein, challenges in the fabrication of full dopant‐free bifacial silicon solar cells are discussed and efficient devices utilizing a MoO3/ indium tin oxide (ITO)/Ag hole‐selective contact and ZnO/LiFx/Al electron‐selective contacts with up to 79% short‐circuit current bifaciality are demonstrated. The ZnO/LiFx/Al rear electron contact features a full‐area ZnO antireflective coating and a LiFx/Al finger contact, allowing sunlight absorption from the back side, thus producing more overall power. The ZnO/LiFx/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The dopant‐free bifacial silicon solar cell has an enhanced bifaciality from ≈20% to 70%, compared to the most recent publication using ZnO/grid‐designed LiF x /Al electron selective contact. [ 37 ] The EQE and the calculated photogenerated current density are also presented from spectral response (shown in Figure S10 , Supporting Information). Compared with EQE results of SHJ solar cell with an impressive efficiency of 24.3%, the spectral response of dopant‐free solar cell in this work is obviously lower at 300–500 nm and 800–1100 nm wavelength band, resulting in a 0.28 and 1.02 mA cm −2 photogenerated current density loss, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The dopant‐free bifacial silicon solar cell has an enhanced bifaciality from ≈20% to 70%, compared to the most recent publication using ZnO/grid‐designed LiF x /Al electron selective contact. [ 37 ] The EQE and the calculated photogenerated current density are also presented from spectral response (shown in Figure S10 , Supporting Information). Compared with EQE results of SHJ solar cell with an impressive efficiency of 24.3%, the spectral response of dopant‐free solar cell in this work is obviously lower at 300–500 nm and 800–1100 nm wavelength band, resulting in a 0.28 and 1.02 mA cm −2 photogenerated current density loss, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…7(c1)), which is capable of receiving scattered and reflected light from the environment for power generation in addition to normal power generation on the front side. 153–157 As shown in Fig. 7(c2), De Bastiani et al 46 found through experiment that the maximum increase in power generation density (PGD) can reach about 7.5 mW cm −2 (bandgap 1.59 eV) as the backside irradiance increases from 0 to 100 mW cm −2 in the case of 1 sun front illumination.…”
Section: Metrics For Practical Applications Of the Psk/c-si Tscmentioning
confidence: 94%
“…For front-back-contacted structures, the highest-efficiency device using a TMO-based hole contact reached 23. and back Si-free contacts were also processed 41,97 with record efficiency for this category of 21.4% using Ag/ITO/MoO 3-x /(i)a-Si:H as a front hole contact and Al/ZnO/LiF x /(i)a-Si:H, achieved by Zhong et al 44 The same structure was used in a bifacial architecture by Lin et al in 2021 and could reach 21 mW/cm 2 in bifacial operation considering 0.15 sun rear irradiance. 228 More complex structures were also explored. Among them, IBC architectures are the most investigated, typically using MoO 3-x in the hole-contact stack.…”
Section: Structures and Their Record Efficienciesmentioning
confidence: 99%